Proteogenomic analysis of the Clostridium difficile exoproteome reveals a correlation between phylogenetic distribution and virulence potential - Quesada Gómez, Carlos (2020)
C. difficile induces antibiotic-associated diarrhea due to the action of two secreted toxins, TcdA and TcdB. A considerable range of virulence among C. difficile strains has been widely reported. During a hospital outbreak, 46 isolates were collected that belonged to different genotypes. Of those, the majority corresponded to two virulent strains, the globally distributed Sequence Type 1 (ST1)_North American Pulsotype 1 (NAP1) and the endemic ST54_NAPCR1 genotypes, respectively. Whereas the virulence of the latter has been attributed to increased secretion of toxins and production of a highly cytotoxic TcdB, these characteristics do not explain the increased lethality of the former. We undertook a proteomic comparative approach of the isolates participating in the outbreak to look for proteins present in the exoproteome of the ST1_NAP1and ST54_NAPCR1 strains. We used a low virulent ST2_NAP4 strain isolated also in the outbreak as control. Dendrograms constructed using the exoproteomes of the strains were very similar to those created using genomic information, suggesting an association between secreted proteins and relative virulence of the strains. By 2D electrophoresis and mass spectrometry it was found that approximately half of the proteins are shared among strains of different genotypes. From the identified proteins, the surface-located SlpA draw our attention due to its detection in ST54_NAPCR1 exoproteomes. Biochemical analysis indicated that the processing of SlpA is different in the ST54_NAPCR1 strain and confirmed that this strain secretes more SlpA than its counterparts. Furthermore, SlpA from the ST54_NAPCR1 strain exerted an increased proinflammatory activity. Altogether, these results indicate that the exoproteome composition correlates with the C. difficile genotype and suggest that particular proteins secreted by some strains could synergize with the effects of TcdA and TcdB increasing their virulence.